The Influence of Value Fit on Safety Performance: A Survey of Employees of Construction Enterprise in Tangshan City, Hebei Province, China - Xinyang, LI; Phakdeephirot, Nutteera (International Journal of Multidisciplinary in Management and Tourism, 2023)
The objectives of this research were to examine (1) the relationship between value fit and safety performance of employees in construction enterprises; (2) the relationship between value fit and self-efficacy of employees in construction enterprises; (3) the relationship between self-efficacy and the safety performance of employees in construction enterprises; and (4) the mediating relationship between value fit and safety performance of employees in construction enterprises. Under the guidance of quantitative research methodology, this research adopts an online questionnaire to conduct an empirical survey. In the context of construction enterprises in Tangshan City, Hebei Province, China, there are 403 employees in construction enterprises with the help of enterprise leaders, colleagues, and friends by simple random sampling method to obtain research data. Data were analyzed using SPSS 24.0 and AMOS 24.0 software, including descriptive statistical analysis, reliability and validity tests, confirmatory factor analysis, and structural equation model analysis. Major Findings were (1) value fit has a significant positive correlation with safety performance; (2) value fit has a significant positive correlation with self-efficacy; (3) self-efficacy has a significant positive correlation with safety performance; and (4) self-efficacy partially mediates the relationship between value fit and safety performance. This research provides a feasible management framework to improve the safety performance of construction enterprises, promote the construction management of engineering projects, and provide practical management suggestions.